MAHATMA GANDHI NATIONAL RURAL EMPLOYMENT GUARANTEE SCHEME AS AN INSTRUMENT OF ASSET CREATION IN MEGHALAYA: A COMPARATIVE STUDY OF MYLLIEM BLOCK AND UMSNING BLOCK (CAHIERS MAGELLANES-NS, 2024)
This paper examines the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) as a pivotal instrument for asset creation in the two Blocks-Mylliem Block of East Khasi Hills District and Umsning Block of Ri-Bhoi District, Meghalaya, India. The MGNREGA being a unique employment programme goes beyond, poverty alleviation, enhancing rural households’ income, curbing gender inequalities and improving the quality of life. It has been particularly transformative in an agrarian poverty driven economy like Meghalaya. Through a review of literature and empirical analysis, this study assesses how MGNREGA has been instrumental in building assets focussing on natural resource management, rural sanitation and rural infrastructure. The finding highlights both successes and challenges in emphasising the role of the program in enhancing rural/local infrastructure, improving livelihoods and fostering sustainable rural development. Key factors influencing the effectiveness of the program and policy implications are discussed and identified to optimise the impact of MGNREGA in the socio-economic context of Meghalaya.